“This Is Not Our Disease”: A Qualitative Study of Influencers of COVID-19 Preventive Behaviours in Nguenyyiel Refugee Camp (Gambella, Ethiopia) - Tsegaye, Ademe; Wilunda, Calistus; Manenti, Fabio; Bottechia, Matteo; D'Alessandro, Michele; Putoto, Giovanni; Atzori, Andrea; Frehun, Daniel; Cardona-Fox, Gabriel (Frontiers in Public Health, 2022)
The COVID-19 pandemic has infected more than 263 million people and claimed the lives of over 5 million people worldwide. Refugees living in camp settings are particularly vulnerable to infection because of the difficulty implementing preventive measures and lack of medical resources. However, very little is known about the factors that influence the behavioural response of refugees towards COVID-19. There is an urgent need for field evidence to inform the design and implementation of a robust social and behaviour change communication strategy to respond to the threat posed by COVID-19 in humanitarian settings. This study examines factors influencing COVID-19-related behavioural decisions in the Nguenyyiel refugee camp located in Gambella, Ethiopia using data collected from focus group discussions and key informant interviews in September 2020. The evidence suggests that while a number of factors have been facilitating the adoption of COVID-19 prevention measures, including good general knowledge about the virus and the necessary preventive strategies and the active engagement by community leaders and non-governmental organisations, important structural and cultural factors have hindered the uptake of COVID-19 prevention measures. These include: difficultly staying at home to minimise physical contact; overcrowding in the camp and within home dwellings; a lack of hand sanitizers and masks and of funds to purchase these; inconsistent use of facemasks when available; COVID-19 denial and misconceptions about the disease, and other cultural beliefs and habits. Overall, the study found that refugees perceived COVID-19 to pose a low threat (susceptibility and severity) and had mixed beliefs about the efficacy of preventive behaviours. This study identified gaps in the existing information education and communication strategy, including a lack of consistency, inadequate messaging, and a limited use of communication channels. While awareness of COVID-19 is a necessary first step, it is not sufficient to increase adoption of prevention measures in this setting. The current communication strategy should move beyond awareness raising and emphasise the threat posed by COVID-19 especially among the most vulnerable members of the camp population. This should be accompanied by increased community support and attention to other barriers and incentives to preventive behaviours.